Religious symbolism in Islamic financial service advertisements. Issue 2 (11th June 2018) - Butt, Muhammad Mohsin; de-Run, Ernest Cyril; U-Din, Ammen; Mutum, Dilip
Abstract : Purpose: This paper aims to examine the impact of increasing the intensity of religious cues in financial service advertisements on target and non-target groups. Design/methodology/approach: To test the proposed hypotheses, a 2 (Religion: Muslims versus Non-Muslims) x 3 (Religious identity primes: Low versus Medium versus High) factorial design was used. Both target and non-target groups were randomly exposed to factitious advertisements of an Islamic bank embedded with low, medium and high intensity of religious cues. Findings: The results of this study indicate that within target group the manipulation did result into a more favourable attitudes towards the advertisement (Aad) and attitudes towards the brand (Ab) for the medium intensity advertisement; however, for high intensity advertisement, only Aad was more favourable compared to low intensity advertisement. Relatively strong evidence was found in case of non-target group negative reactions in term of Aad, Ab and purchase intention. The direct comparison between target and non-target groups suggest a general pattern of more positive response from target group as compared to non-target group. Practical implications: The findings of this study provide an important insight into the effectiveness of identity salience messages in financial service marketing. The study provide empirical evidence that intensifying the rhetoric beyond a certain point will generate negative results from both target and non-target respondents. Originality/value: The authors integrated the research on symbolism, social identity and target and non-target effects to analyse the attitudinal and behavioural differences between and within target and non-target groups of financial service advertisements with different intensity of religious cues.